Sibling similarity in income: A life course perspective. (April 2022) - Grätz, Michael; Kolk, Martin
Abstract: Sibling similarity in income is a measure of the omnibus effect of family and community background on income. We estimate sibling similarity in income accumulated over the life course (ages 18 to 60) to demonstrate that previous research has underestimated sibling similarity in income. Using high-quality Swedish register data, we find sibling similarity in accumulated, lifetime income to be much higher than sibling similarity in income measured over a short number of years. In addition, we test theories predicting variation in sibling similarity over the life course. We find that, contrary to predictions derived from the model of cumulative advantage, sibling similarity in accumulated income is largely stable over the life course. Sister correlations in income are lower than brother correlations but differences diminish across cohorts. We also find largely the same amount of sibling similarity in accumulated income in socioeconomically advantaged and disadvantaged families. We conclude by discussing the importance of using accumulated income for understanding trends and mechanisms underlying the omnibus effect of family and community background on income.